Interferon Gamma-Inducible Protein 16 of Peripheral Blood Mononuclear Cells May Sense Hepatitis B Virus Infection and Regulate the Antiviral Immunity - Lu, Yu-Qing; Wu, Jing; Wu, Xiang-Ji; Ma, Hui; Ma, Yan-Xiu; Zhang, Rong; Su, Meng-Nan; Wu, Nan; Chen, Gong-Yin; Chen, Hong-Song; Pan, Xiao-Ben (Frontiers in Cellular and Infection Microbiology, 2021)
Interferon gamma-inducible protein 16 (IFI16) is a DNA sensor protein, which triggers interferon-beta (IFN-β) production. However, the role of IFI16 in the innate immunity against hepatitis B virus (HBV) remains controversial. Peripheral blood mononuclear cells (PBMCs) and serum specimens were collected from 20 patients with chronic hepatitis B (CHB) receiving Peg-IFN-α2b therapy. IFI16 mRNA/protein of PBMCs and serum IFI16 at baseline and changes during Peg-IFN-α2b treatment were detected. The interaction between IFI16 and HBV DNA in the PBMCs was analyzed using chromatin immunoprecipitation assay. Leukemic T cell line CEM-C7 and HBV-replicating HepG2.2.15 cells were used to test the effects of interferon treatment and HBV replication on IFI16 expression. Compared with healthy controls, lower levels of IFI16 mRNA but more significant expression of IFI16 protein with heterogeneous degradation were detected in PBMCs of CHB patients. Early changes in IFI16 mRNA, but not IFNB mRNA of PBMCs or serum IFI16, were correlated to HBeAg seroconversion of Peg-IFN-α2b therapy. An interaction between IFI16 and HBV DNA was detected in the PBMCs. In the cultured HepG2.2.15 and CEM-C7 cells, interferons resulted in the translocalization of IFI16 from the cytoplasm to the nucleus and inhibited IFI16 degradation. IFI16 of PBMCs may play a role in sensing HBV infection, and early change in IFI16 mRNA of PBMCs is valuable to predict HBeAg seroconversion in Peg-IFN-α2b treatment. The influences on IFI16 degradation and subcellular location may present a molecular mechanism of antiviral activity of interferon.